Breast Conservation Surgery: State of the Art - Jonathan White; Raj Achuthan; Philip Turton; Mark Lansdown (International Journal of Breast Cancer)
Breast conservation surgery is available to the vast majority of women with breast cancer. The combination of neoadjuvant therapies and oncoplastic surgical techniques allows even large tumours to be managed with a breast-conserving approach. The relationship between breast size and the volume of tissue to be excised determines the need for volume displacement or replacement. Such an approach can also be used in the management of carefully selected cases of multifocal or multicentric breast cancer. The role of novel techniques, such as endoscopic breast surgery and radiofrequency ablation, is yet to be precisely defined.